THE TRANSLATION OF SALADIN AL AYYUBI: A STUDY OF METHODS, CLARITY, AND AUDIENCE RESPONSE - Gunawan, Oktaviona Eka putri; Syihabuddin, Syihabuddin; Maulani, Hikmah (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2024)
The purpose of this research is to reveal the clarity of the translation in the movie Saladin Al-Ayyubi. This research uses a qualitative approach with document analysis method. The data used in this study came from the dialog sentences of the two characters' speech in the subtitle of Saladin Al-Ayyubi episode 4 on the Arabic Cartoon YouTube channel and the results of a survey conducted on respondents totaling 21 participants. To collect data, the researcher watched and observed the movie Saladin Al-Ayyubi repeatedly to transcribe the movie. After that, the researcher distributed questionnaires to classify and analyze the types of methods, clarity, and audience responses to the Arabic - Indonesian translation in the Salahuddin Al-Ayyubi film. The findings of this study are the types of methods used in the Arabic - Indonesian translation of Saladin Al-Ayyubi movie and the level of clarity of the methods used according to the audience. The researcher found five out of eight Newmark methods used in the translation, namely (1) word-by-word method; (2) semantic method; (3 free method; (4) literal method; and (5) communicative method. The level of intelligibility in the Arabic - Indonesian subtitles of Saladin Al-Ayyubi movie shows that 19% of the text is at a low level of legibility, 59% of the text is at a medium level of legibility, and 22% of the text is at a high level of legibility.